Cure of Helicobacter pylori infection in patients with reflux oesophagitis treated with long term omeprazole reverses gastritis without exacerbation of reflux disease: results of a randomised controlled trial. Issue 1 (18th December 2003) - Kuipers, E J; Nelis, G F; Klinkenberg-Knol, E C; Snel, P; Goldfain, D; Kolkman, J J; Festen, H P M; Dent, J; Zeitoun, P; Havu, N; Lamm, M; Walan, A
Abstract : Background: Helicobacter pylori gastritis may progress to glandular atrophy and intestinal metaplasia, conditions that predispose to gastric cancer. Profound suppression of gastric acid is associated with increased severity of H pylori gastritis. This prospective randomised study aimed to investigate whether H pylori eradication can influence gastritis and its sequelae during long term omeprazole therapy for gastro-oesophageal reflux disease (GORD). Methods: A total of 231 H pylori positive GORD patients who had been treated for ⩾12 months with omeprazole maintenance therapy (OM) were randomised to either continuation of OM (OM only; n = 120) or OM plus a one week course of omeprazole, amoxycillin, and clarithromycin (OM triple; n = 111). Endoscopy with standardised biopsy sampling as well as symptom evaluation were performed at baseline and after one and two years. Gastritis was assessed according to the Sydney classification system for activity, inflammation, atrophy, intestinal metaplasia, and H pylori density. Results: Corpus gastritis activity at entry was moderate or severe in 50% and 55% of the OM only and OM triple groups, respectively. In the OM triple group, H pylori was eradicated in 90 (88%) patients, and activity and inflammation decreased substantially in both the antrum and corpus (p<0.001, baseline v two years). Atrophic gastritis also improved in the corpus (p<0.001) but not in the antrum. In the 83 OM only patients with continuing infection, there was no change in antral and corpus gastritis activity or atrophy, but inflammation increased (p<0.01). H pylori eradication did not alter the dose of omeprazole required, or reflux symptoms. Conclusions: Most H pylori positive GORD patients have a corpus predominant pangastritis during omeprazole maintenance therapy. Eradication of H pylori eliminates gastric mucosal inflammation and induces regression of corpus glandular atrophy. H pylori eradication did not worsen reflux disease or lead to a need for increased omeprazole maintenance dose. We therefore recommend eradication of H pylori in GORD patients receiving long term acid suppression.